2017
DOI: 10.1002/cam4.1100
|View full text |Cite
|
Sign up to set email alerts
|

A state‐wide initiative to promote genetic testing in an underserved population

Abstract: Genetic testing for cancer susceptibility has been widely studied and utilized clinically. Access to genetic services in research and practice is largely limited to well‐insured, Caucasian individuals. In 2009, the Cancer Resource Foundation (CRF) implemented the Genetic Information for Treatment Surveillance and Support (GIFTSS) program to cover the out‐of‐pocket expenses associated with cancer genetic testing, targeting high‐risk individuals with limited financial means and limited health insurance coverage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Other studies demonstrated health inequalities for patients from high‐poverty neighborhoods . These inequalities may be amplified in rare genetic diseases, as access to subspecialty care and genetic testing may be challenging for low‐income patients …”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated health inequalities for patients from high‐poverty neighborhoods . These inequalities may be amplified in rare genetic diseases, as access to subspecialty care and genetic testing may be challenging for low‐income patients …”
Section: Discussionmentioning
confidence: 99%
“…Following resolution of any discrepancies between reviewers, 83 publications were included in the final review (ordered alphabetically by primary author in Table 1). 8–90 A flow diagram tracking the number of studies at each stage of the selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the eighty‐three publications included in the review (Table 1), 8–90 seventy‐five (90.4%) were published since 2010 inclusive, and 48 (57.8%) since 2016 inclusive (Figure 2). The majority of studies were carried out in the United States ( n = 66; 79.5%), followed by the United Kingdom ( n = 5; 6.0%), Canada ( n = 3; 3.6%), and Australia ( n = 2; 2.4%) (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Racial and ethnic minorities are among the underserved populations for genetic services in the United States. These populations have reduced access to genetic testing, 22 and medical mistrust results in underutilization of genetic counseling and testing. [23][24][25][26] As a result of this history, genetic databases are largely composed of individuals of European ancestry.…”
Section: Social Justice and Equitymentioning
confidence: 99%